Redes sociais virtuais: uma proposta de escola expandida - Hardagh, Cláudia Coelho (2009)
This thesis presents the research and study on Social Networks and Web 2.0, assesses its features and potential as a learning space that will be called Escola Expandida (Expanded School). The research and analysis are theoretically anchored on the thoughts of Lev Semionovitch Vygotsky, Mikhail Bakhtin and Lucia Santaella, who have in common valuing the dialogic relationship as a knowledge building space and the importance of language in man s social, cultural and historical building-up. I have searched for inspiration art and artists as creative professionals who cause cultural changes along our history. Using art as an inspiration served as support to encourage educators to dare and create strategies to change the school practice that involves the school s program, space and time. In order to make the study, which is of qualitative nature, it was used data gathered from May 2007 to March 2008, spontaneous testimonies from focal groups formed by Fashion Design, Multimedia Production Technicians and Visual Communications students from the SENAC College Center. From these groups emerged the following categories: language, ethics and aesthetics and the theoretical category expanded cognition, which was assessed a priori. To analyze the latter a questionnaire was also applied to the Fashion Design students. The Escola Expandida to the social networks was proposed based on the analysis of the current historical context - cyberculture and the 21st. century youngsters cyberyoungsters inserted in such context. The study was developed combining the data gathered in the students testimonies and the theories presented by the aforementioned thinkers and relevant authors in the Education and Technology and Art area. The students assigned senses to the social networks and Web 2.0 as important spaces for sociability, sharing information and cooperation also oriented towards producing knowledge, but at the same time they valued the school, books and being physically together. When shaping and developing the testimonies, I observed that most of the cyberyoungsters value the traditional education methods and understand the need to aggregate the technological potential to the educational practices. This shows the possibility of aggregating resources and new spaces, ratifies the Escola Expandida proposal that is part of the traditional schools to the virtual social networks and introduces the open cybergeneration thinking to circulate in all information and communication spaces, but indicates that changes have to be made and are related to the program, the updating of information that books don t follow, to valuing new kinds of aesthetics and ethics based on exchanging and in cooperation environments with characters that are not part of the school institution